1991
DOI: 10.1063/1.859791
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of magnetic field fluctuations during dynamo activity and its effect on energy confinement in a reversed-field pinch

Abstract: Fluctuations of magnetic fields and related magnetohydrodynamic (MHD) phenomena are investigated in the TPE-1RM15 reversed-field pinch experiment [Plasma Physics and Controlled Fusion Research, 1986 (IAEA, Vienna, 1987), Vol. 2, p. 453]. Mode analysis of fluctuations measured by multichannel coils reveals that nonlinear interactions between m=1 and m=0 modes, such as nonlinear coupling and phase locking, play significant roles during a dynamo event (i.e., the flux genertion process in the sustainment phase), r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
27
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 27 publications
5
27
0
Order By: Relevance
“…This behavior is reminiscent of the socalled "slinky mode" generated by the nonlinear phase locking of tearing modes in reversed-field pinches. [39][40][41][42] V. TOROIDAL COUPLING OF TWO NEOCLASSICAL TEARING MODES…”
Section: Phase-locked Statementioning
confidence: 99%
“…This behavior is reminiscent of the socalled "slinky mode" generated by the nonlinear phase locking of tearing modes in reversed-field pinches. [39][40][41][42] V. TOROIDAL COUPLING OF TWO NEOCLASSICAL TEARING MODES…”
Section: Phase-locked Statementioning
confidence: 99%
“…Besides the simplest theoretical prediction based on the dimensionless Ohm's law,b B~S 21͞2 , quite a wide effort has been dedicated to investigate the behavior of magnetic fluctuations in the RFP [4][5][6][7][8][9][10][11][12]: exponents a for theb B~S 2a scaling law have been found ranging from a ഠ 0.07 to a ഠ 0.5. In particular, in a recent paper Stoneking et al [11] have extended the range of S over which the scaling is experimentally studied and they have proposed a narrow range of measured exponents a, i.e., 0.07 # a # 0.18, depending on the density regime.…”
mentioning
confidence: 99%
“…29 The observations of discrete relaxation in the RFP plasmas showed that the relaxation may go on in an oscillatory manner. The loop voltage, reversal parameter, and electron current all have sawtooth character [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] during the relaxation. The loop voltage and fluctuation amplitudes peak at the sawtooth crash.…”
Section: Jϭ"؋bϭb ͑1͒mentioning
confidence: 99%
“…63. Since the MHD dynamo action was introduced into the RFP plasma, 55 the MHD dynamo theory has enjoyed considerable success in the physics of the laboratory plasma and is well supported by the experimental phenomenology [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] and the numerical simulations. 66 -77 It is of great importance to the physics of the RFP plasma that the MHD dynamo electric field and mean-field Ohm's law have been verified in the recent experiment.…”
Section: Jϭ"؋bϭb ͑1͒mentioning
confidence: 99%
See 1 more Smart Citation